Til lykke - Jarvad, Pia (Folia Scandinavica Posnaniensia, 2016)
In this article I give semantic and historical explanations of some selected lexical areas that may cause problems for non-native speakers of Danish. I describe some important developments in a historical perspective, showing how new words shift the semantics of old words. I also deal with how many new words are continuously recorded and the vast majority of new words are occasional formations. They show the creativity in Danish language. I have selected two new words from each year since 1946 to honor the 70-year-old professor in Danish.